2022
DOI: 10.1002/hsr2.656
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood group with in‐hospital adverse outcome and long term persistent symptoms of COVID‐19 infection: A single‐center longitudinal observational study

Abstract: Background and Aims: There are gaps in knowledge regarding the association between the ABO blood group and coronavirus disease 2019 (COVID-19) immediate and long-term outcomes. We aimed to investigate the association of ABO blood group with COVID-19 in-hospital adverse outcomes and to determine whether ABO blood group is associated with post-COVID-19 persistent symptoms.Methods: This was a single-center longitudinal observational study that included patients who presented with symptoms suggestive of COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(83 reference statements)
0
7
0
2
Order By: Relevance
“…Conversely, El-Shitany et al reported an association between blood type O and unfavorable outcomes, such as lower oxygen saturation and mechanical ventilation requirement, while blood type A was linked to lower odds of requiring artificial ventilation, and blood type B, to shorter recovery periods [ 51 ]. Significant associations with severity [ 84 ] and mortality [ 69 , 89 ] were also reported for blood type B, while blood type AB has been linked to either favorable [ 84 ], or unfavorable [ 89 ] outcomes. More recently, some studies sought to investigate whether ABO blood types are associated with long-term symptoms presentation after COVID-19 recovery.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, El-Shitany et al reported an association between blood type O and unfavorable outcomes, such as lower oxygen saturation and mechanical ventilation requirement, while blood type A was linked to lower odds of requiring artificial ventilation, and blood type B, to shorter recovery periods [ 51 ]. Significant associations with severity [ 84 ] and mortality [ 69 , 89 ] were also reported for blood type B, while blood type AB has been linked to either favorable [ 84 ], or unfavorable [ 89 ] outcomes. More recently, some studies sought to investigate whether ABO blood types are associated with long-term symptoms presentation after COVID-19 recovery.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…More recently, some studies sought to investigate whether ABO blood types are associated with long-term symptoms presentation after COVID-19 recovery. Blood type AB was significantly associated with long-term palpitation and dizziness [ 89 ], and blood type O, with subjective loss of smell [ 90 ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…44 According to a similar study done in Iraq, the blood type AB is substantially more likely than other blood types to require respiratory support, experience persistent palpitations, and dizziness. 45 The risk of intubation and/or mortality was found to be high with the “AB” blood group and low with the “A” blood group by Zietz et al when they investigated the relationship between the severity of COVID-19 and the ABO blood group system. 41 While Ad’hiah et al termed the “AB” blood type as a possible biomarker for COVID-19 susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Discordant results have been published on the association between sequelae and complications post-COVID-19 and ABO, with the B-group [ 21 ], O-group [ 22 ], or AB-group [ 23 ] associated with more risk of complications.…”
Section: Introductionmentioning
confidence: 99%